Живучість та стійкість функціонування компонентів інформаційних систем розумного міста - Василенко, М. Д.; Василенко, Микола Дмитрович; Бойко, Віктор Дмитрович; Бойко, В. Д.; Слатвінська, Валерія Микoлaївна; Слатвінська, В. М. (My University, 2021)
У статті досліджуються проблеми живучості та стійкості функціонування компонентів інформаційних систем розумного міста. Авторами проаналізовано ситуацію із сучасними інтегрованими системами різного рівня інформаційної екосистеми розумного міста. Запропонована авторами альтернативна модель розвитку систем спирається на досвід впровадження та розробки наявних рішень глобальних інформаційних систем.

The article examines the problems of survivability and stability of functioning of components of Smart City Information Systems. The relevance of the topic is related to the wide dissemination and implementation of information and communication technologies at various levels. The degree of relevance is great. The authors analyze the situation with modern integrated systems of various levels of the smart city information ecosystem. One of the main problems of implementing smart home systems is the fragmentation and fragmentation of the market - each manufacturer seeks to lock the user to its standard, which leads to the lack of uniform standards of interaction. As a result, the usability of smart home systems worsens, the cost of ownership and support increases, and the security of their use decreases – including potentially increasing the area of cyberattacks. In addition, disparity in standards and vendor lock-in lead to excessive complexity of interaction between smart home systems and the smart city information ecosystem. All of the above pushes users away from the existing market and leads to a decrease in sales, which leads to stagnation in this market segment. The alternative model of system development proposed by the authors is based on the experience of implementing and developing existing solutions for Global Information Systems. The solution should be based on open interaction protocols at all levels of the information ecosystem, which will allow manufacturers to develop their product taking into account and in the context of interaction with other products. The construction of modules and components of such a system is considered separately. ideally, each of the smart home modules should not lose its qualities both in the context of the Smart Home information ecosystem and outside it.
Василенко М. Д. Живучість та стійкість функціонування компонентів інформаційних систем розумного міста / М. Д. Василенко, В. Д. Бойко, В. М. Слатвінська // Науково-технічний збірник «Комунальне господарство міст». Серія: технічні науки та архітектура. - Том. 6, № 166. - 2021. - С. 20-27. DOI:10.33042/2522-1809-2021-6-166-20-27
Keywords: «розумне місто»; міське господарство; комп’ютерні технології; інформаційні системи; "smart city"; urban economy; computer technologies; information system; Research Subject Categories::TECHNOLOGY